2019
DOI: 10.1101/536466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutational analysis of field cancerization in bladder cancer

Abstract: 31By applying whole exome sequencing and deep targeted sequencing on bladder 32 tumors, it was recently shown that tumors developed years apart in the same patients 33 share multiple mutations and hence are clonally related 1-3 . Furthermore, apparently 34 normal urothelium has been documented to contain mutations with low allele 35 frequencies (~3%) that are typically observed at high frequencies in tumors (clonal 36 mutations) 1-3 . Multiple studies have investigated genomic alterations in normal 37 ap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Such a genetic heterogeneity has been found in the premalignant lesions in Barrett's esophagus, 5 and has been linked to progression of breast tumors. 37 The most detailed genetic studies of the premalignant urothelium has been done in research groups of Dyrskjøt,8,9 and Czerniak. 6,7 Both groups have used multiregion sampling from whole organs to identify tumor-associated mutations in the noncancerous epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a genetic heterogeneity has been found in the premalignant lesions in Barrett's esophagus, 5 and has been linked to progression of breast tumors. 37 The most detailed genetic studies of the premalignant urothelium has been done in research groups of Dyrskjøt,8,9 and Czerniak. 6,7 Both groups have used multiregion sampling from whole organs to identify tumor-associated mutations in the noncancerous epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…5 Studies on the genetic heterogeneity of the premalignant field in patients with urothelial bladder cancer (UBC) have given important insights into the processes behind tumor initiation and favor a clonal origin. [6][7][8][9] The shared clonal origin of nonmuscle invasive bladder cancer (NMIBC) recurrences has been repeatedly demonstrated [10][11][12] even though tumors usually occur in different locations within the bladder. 13 Taken together, a model is supported in which tumors develop semiindependently out of a premalignant field that is usually clonal in nature but has additional heterogeneity that manifests as genetic differences between recurrences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indeed observed clonal expansion of mutant cells in morphologically normal urothelium. In one study on four patients, intriguingly, KMT2D, another COMPASS component, was frequently mutated in morphologically normal urothelial tissue from cancer-carrying bladders [34]. An analogous scenario is established in the development of acute myeloid leukemia, which is often preceded by clonal hematopoiesis elicited by mutations in various genes, most often encoding epigenetic regulators like DNMT3A and TET2 [35], which shift the balance between stem cells and differentiated progeny and displace normal with stem cells with mutants.…”
Section: Discussionmentioning
confidence: 97%